2019
DOI: 10.1002/etc.4366
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of polycyclic aromatic hydrocarbons by arctic and temperate benthic species

Abstract: Increasing oil and gas activities may substantially increase chemical stress to benthic ecosystems in the Arctic, and it is necessary to evaluate such environmental risks in these systems. Risk assessment procedures for oil‐related compounds (e.g., polycyclic aromatic hydrocarbons [PAHs]) should address differences in exposure between Arctic and temperate benthos. We compare for the first time the bioaccumulation of PAHs by Arctic benthic invertebrate species with that of temperate species, based on their biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 82 publications
(173 reference statements)
1
2
1
Order By: Relevance
“…10, lowest panel). This was also found in earlier studies where BSAFs of PAHs were generally low (BSAF < 1) (Szczybelski et al, 2019). BSAF values for the Lovénbreen and Krossfjorden were closer together (0.4-1.0 and 1.0-1.5).…”
Section: Marine Biotasupporting
confidence: 88%
“…10, lowest panel). This was also found in earlier studies where BSAFs of PAHs were generally low (BSAF < 1) (Szczybelski et al, 2019). BSAF values for the Lovénbreen and Krossfjorden were closer together (0.4-1.0 and 1.0-1.5).…”
Section: Marine Biotasupporting
confidence: 88%
“…However, the PAH levels were quite similar to what was found for benthic invertebrates in Kongsfjorden, Svalbard [54], and also to what Thuy et al [55] reported as common for various bivalves in the ocean. The concentrations in the invertebrates of the present study were furthermore quite below potential bioaccumulation levels reported for high-exposure scenarios for arctic and temperate marine invertebrates reported by Szczybelski et al [56]. A PCA of invertebrates from the SWRPs (18 biota samples distributed on 4 taxa, Table 1) and the natural, shallow lakes (19 biota samples distributed on 4 taxa) showed that PC1 accounted for 30.1% of the total variance, whereas PC2 accounted for 19.7% (Figure 4).…”
Section: Invertebratescontrasting
confidence: 85%
“…Due to it has induced the highest number of revertants acenaphthylene (ACY), acenaphthene (ACE), fluorene (FLU), phenanthrene (PHE), and anthracene (ANT) were detected in all analyzed samples with maximum concentrations ranging from 0.800 µg g −1 dry weight (dw) (ANT) to 7.14 µg g −1 dw (PHE). These values were similar to those presented by Szczybelski et al 37 which reported LMW PAH concentrations in the range of 0.149 µg g −1 dw (ANT) to 2.46 µg g −1 (PHE) and 0.100 µg g −1 dw (ANT) to 2.28 µg g −1 dw (PHE) for polychaetes Nephtys ciliata and Alitta virens, respectively. In that study the authors analyzed the PAH content in polychaetes living in impacted sediment collected in Oosterchelde Estuary, Netherlands.…”
supporting
confidence: 91%